2021
DOI: 10.1007/s11695-021-05374-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Favorable Changes in Food Preferences After Bariatric Surgery

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…It will be important to determine through direct measures whether the food preference shifts described here in rodents are also evident in humans. Recent studies suggest otherwise, but more work needs to be done ( 3 , 13 , 29 , 30 ). Further understanding of the impact of bariatric operations on food preferences will certainly improve preoperative counseling and may help to optimize surgical outcomes ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be important to determine through direct measures whether the food preference shifts described here in rodents are also evident in humans. Recent studies suggest otherwise, but more work needs to be done ( 3 , 13 , 29 , 30 ). Further understanding of the impact of bariatric operations on food preferences will certainly improve preoperative counseling and may help to optimize surgical outcomes ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies that have applied more direct measures of food intake and choice have found little to any change in food selection or relative macronutrient energy intake ( 3 , 29 ). On the other hand, in an ad libitum buffet meal test setting, administered preoperatively and at 6-month after BS, favorable changes in food preferences can be predicted with the use of a combination of factors, including genetic, psychologic and social patient characteristics ( 30 ). Beyond changes in food preferences, RYGB results also in lower average meal size.…”
Section: Introductionmentioning
confidence: 99%
“…Besides a reduction in caloric intake, many clinical studies also report changes in food preferences and food choice, as well as in the ‘liking’ and ‘wanting’ of specific nutrients and foods after bariatric surgery [ [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] ]. Homeostatic mechanisms centering around the hypothalamus have been dominating research in the 20th century, but there is now much interest in the role of hedonic and cognitive brain functions in the controls of food intake and regulation of energy balance [ [138] , [139] , [140] ].…”
Section: Bariatric Surgery Changes Gut-brain Communicationmentioning
confidence: 99%
“…Patients report feeling less hunger and consuming fewer calories, especially foods high in sugar and fat [4,[12][13][14][15][16][17]. There are also some indications that patients find the taste of these foods less appealing [18][19][20][21][22]. However, while self-reporting methods of measuring food intake have utility, they are vulnerable to mis-reporting, particularly under-reporting and are unlikely to be representative of usual food intake [23][24][25].…”
Section: Introductionmentioning
confidence: 99%